A study of the radiation tolerance of poly-crystalline and single-crystalline CVD diamond to 800 MeV and 24 GeV protons. (30th August 2019) - Bäni, L; Alexopoulos, A; Artuso, M; Bachmair, F; Bartosik, M; Beck, H; Bellini, V; Belyaev, V; Bentele, B; Bes, A; Brom, J-M; Bruzzi, M; et al.
Abstract: We have measured the radiation tolerance of poly-crystalline and single-crystalline diamonds grown by the chemical vapor deposition (CVD) process by measuring the charge collected before and after irradiation in a 50 m pitch strip detector fabricated on each diamond sample. We irradiated one group of sensors with 800 MeV protons, and a second group of sensors with 24 GeV protons, in steps, to protons cm −2 and protons cm −2 respectively. We observe the sum of mean drift paths for electrons and holes for both poly-crystalline CVD diamond and single-crystalline CVD diamond decreases with irradiation fluence from its initial value according to a simple damage curve characterized by a damage constant for each irradiation energy and the irradiation fluence. We find for each irradiation energy the damage constant, for poly-crystalline CVD diamond to be the same within statistical errors as the damage constant for single-crystalline CVD diamond. We find the damage constant for diamond irradiated with 24 GeV protons to be and the damage constant for diamond irradiated with 800 MeV protons to be . Moreover, we observe the pulse height decreases with fluence for poly-crystalline CVD material and within statistical errors does not change with fluence for single-crystalline CVD material for both 24 GeV proton irradiation and 800 MeV proton irradiation. Finally, we have measured the uniformity of each sample as a function of fluence and observed that for poly-crystalline CVD diamond the samples become more uniform with fluence while for single-crystalline CVD diamond the uniformity does not change with fluence.